Encantos e desencantos em Camaputiua: conflitos agrários e resistência quilombola. - Silva, Vanessa Cristina Ramos Fonsêca da (2020)
This dissertation aims to analyze agrarian conflicts in the Quilombola Territory of Camaputiua. Its presentation starts from the terms “charms” and “disenchantments” of human rights formulated by Rubio (2014). According to the author, the “charms” consist of the emancipatory dimension of human rights, when one sees the liberation of the instruments of domination that prevent the realization of these rights. However, it presents a counterpoint to these “charms”, which are the “disenchantments”. They consist of the difficulty in implementing human rights, as they are only based on theories, while the reality is totally different from the legal provisions. Soon, the legislation related to quilombolas was cataloged, evidencing the Federal Constitution of 1988 and Convention No. 169 on indigenous and tribal peoples of the International Labor Organization. Then, the challenges for the implementation of these rights and the conflicts experienced by quilombolas due to these “disenchantments” were exposed, as well as the difficulty of access to the justice systems. It also discusses the resistance strategies of quilombolas in the face of these conflicts, showing the attempt to break with the system of domination and breaking the stigma of victimization. Finally, the strong presence of the African religion was highlighted, which is also considered a “charm” due to the close relationship between the enchanted and the quilombolas. Such results were obtained from the analysis of vast bibliographic and documentary material, as well as collected in field research, through direct observation, interviews, and conversations with various social agents. The critical analysis of this material was essential to obtain the results achieved.